Hybrid photography : intermedial practices in science and humanities - Hillnhuetter, Sara; Klamm, Stefanie; Tietjen, Friedrich (Routledge history of photography, 2021)
"This book explores the territories where manual, graphic, photographic, and digital techniques interfere and interlace in sciences and humanities. It operates on the assumption that when photography was introduced, it did not oust other methods of image production but rather became part of ever more specialized and sophisticated technologies of representation. The epistemological break commonly set with the advent of photography since the nineteenth century probably has been triggered by photographic techniques but certainly owes much to the availability of a plethora of hybrid media - media that influence the relation of sciences, humanities, and their methods and subjects. This book will be of interest to scholars in art and visual culture, photography, and history of photography"- Resumé vydavatel